A camouflage coating with similar solar spectrum reflectance to leaves based on polymeric inorganic composite - Ying Gao; Bo Tang; Guojian Ji; Kang Chen; Zhengwei Wang; Hong Ye (Materials Research Express, 2021)
To realize the hyperspectral camouflage under the background of vegetation, a camouflage polyvinyl alcohol coating containing lithium chloride and green pigment particles of chromium sesquioxide (Cr _2 O _3 ) was prepared on a stainless-steel substrate. Based on the four flux Kubelka-Munk model, the reflectances of the coatings with different volume fractions of Cr _2 O _3 ( f _c ) were predicted and compared with those of the membranes without substrate. The results show that when f _c reaches 0.8%, the 0.2 mm thick coating can conceal the reflectance characteristics of the stainless-steel substrate. The reflectances of the coatings with the volume fraction of water ( f _w ) in the range from 0% to 50% were also calculated via the model. It is found that the reflectances around 1460 nm and 1940 nm decrease with increased f _w due to the significantly enhanced absorption coefficient, and the correlation coefficient between the spectral reflectances of the camouflage coating and an Osmanthus fragrans leaf increases from 0.913 to 0.954, indicating that the coating camouflage performance can be improved by increasing f _w .